The Impact of Mobile Phone Use on Student Learning Achievement Results in the Subject of Aqidah Akhlak at MI Al Mujahidin, Satui District, Tanah Bumbu Regency - Muhammad Bahrudin; Lutfia Intan Cahyani; Khofifah Indar Parawansa; Usnul Mukarramah Syam; Lina Syakira; Melvi Maulida (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research is based on the formulation of the problem, namely, what are the impacts of mobile phone use on student learning achievement at MI Al Mujahidin, Satui District, Tanah Bumbu Regency and what factors influence the learning achievement of students at MI Al Mujahidin, Satui District, Tanah Bumbu Regency. In this study, the subjects were sixth grade students at MI Al Mujahidin, Satui District, Tanah Bumbu Regency, totaling eleven students, while the object of this study was the impact of mobile phone use on the learning outcomes of sixth grade students in the subject of Aqidah Akhlak at MI Al Mujahidin, Satui District, Tanah Bumbu Regency. In collecting this data, the author used qualitative methods, data collection techniques with interviews, observation and documentation. While data processing techniques with editing and qualification techniques. So the results of this study are, the impact of mobile phone use does not have a negative effect on student learning achievement, even students are responsible for completing assignments and homework given by teachers on time and getting good grades. And the factors that support students to achieve are environmental factors and support from parents as the first educators and also as people close to the students.